2010
DOI: 10.1021/ef901218w
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Liquefaction of Woody Biomass in Hot-Compressed Alcohol−Water Co-solvents

Abstract: Alcohol (methanol or ethanol) and water showed synergistic effects on biomass direct liquefaction, and the 50 wt % co-solvent of either methanol-water or ethanol-water was found to be the most effective solvent for the liquefaction of eastern white pine sawdust. The 50 wt % aqueous alcohol at 300°C for 15 min produced a bio-oil yield at approximately 65 wt % and a biomass conversion of >95%. At a temperature higher than 300°C, conversion of bio-oil to char was significant by repolymerization. The Fourier trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
170
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 269 publications
(195 citation statements)
references
References 51 publications
19
170
1
2
Order By: Relevance
“…Huang et al found that carrying out a similar lignin depolymerization process in ethanol instead of methanol using a Cu-Mg-Al mixed oxide catalyst resulted in higher aromatics yield and less char by-product [8][9][10]. The better performance in ethanol is in keeping with an earlier report by Cheng et al [16].…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Huang et al found that carrying out a similar lignin depolymerization process in ethanol instead of methanol using a Cu-Mg-Al mixed oxide catalyst resulted in higher aromatics yield and less char by-product [8][9][10]. The better performance in ethanol is in keeping with an earlier report by Cheng et al [16].…”
supporting
confidence: 62%
“…This was confirmed in the work of Huang et al [9]. Overall, the aromatic monomers yields are higher when depolymerization of lignin is carried out in ethanol than in methanol [16,19,20]. Ethanol has several functions: it dissolves lignin, it chemically protects the useful lignin fragments against undesired repolymerization by alkylation of aromatic rings and phenolic groups and it is a source of hydrogen to facilitate the hydrogenative removal of oxygen functionalities from the fragments [8].…”
mentioning
confidence: 70%
“…Both AV rind and AV pulp fibers had a high amount of ash that was slightly lower than ash content (8.89 %) in AV rind with cuticle (Cheng et al 2014) but much higher than 0.4% in wood (Cheng et al 2010). The AV rind without cuticle presented a high amount of α-cellulose of 50.05 % that was even higher than 40.2% in wood (Cheng et al 2010). The α-cellulose identified in AV pulp fibers was remarkably increased to 77.22%.…”
Section: Effect Of Process Of Isolation Of Aloe Vera Nanofibers On Tementioning
confidence: 87%
“…Meanwhile, the absorption profiles between 690 cm -1 and 930 cm -1 implied the presence of phenyl rings and substituted phenyl rings (Cheng et al 2010). The peak at 1050 cm -1 appeared in the absorption profile of bamboo and solid residue, which could be C-O connected with hydroxyl groups and were dehydrated after liquefaction.…”
Section: Ft-ir Analysismentioning
confidence: 98%